Physicochemical parameters, anti-nutritional factors, vitamin and mineral contents of rubus steudneri and rubus apetalus leaves - Raghavendra, H. L. [UNESP]; Prashith Kekuda, T. R.; Chetan, D. M.; Shantaram, Manjula (My University, 2020)
Introduction and Aim: Rubus steudneri Schweinf. and Rubus apetalus Poir. are two of the three Rubus species that grow in Ethiopia belongs to the Rosaceae family consumed as food and used in traditional medicine. Studies of this species have been restricted to in vitro antioxidant studies. Keeping this into consideration, we determined physicochemical characteristics, anti-nutritional, anthocyanin, vitamin, and mineral contents of R. steudneri and R. apetalus leaves. Materials and Methods: Physicochemical characteristics such as moisture, pH, total ash, acid-insoluble ash, and extractive values were determined. Anthocyanin content and anti-nutritional factors namely phytic acid and tannins were estimated. The content of vitamins namely vitamin C, thiamine, pyridoxine, niacin, and cyanocobalamin were also estimated using HPLC. Furthermore, major and minor elements including toxic heavy metals were determined using ICP-OES. Results: Total ash and acid-insoluble ash content were highest in R. steudneri and R. apetalus, respectively. The extractive values recorded were higher for methanol followed by aqueous, alcohol, and petroleum ether. R. apetalus contained more quantity of phytic acid, tannin and anthocyanin than R. steudneri. Both the plants contained vitamins namely niacin and pyridoxine, whereas thiamine, vitamin C, and cyanocobalamin were not detected. The content of calcium, potassium and magnesium were found to be highest among major elements. In case of minor elements, the content of iron, zinc, and copper were highest when compared to nickel. Furthermore, heavy metals like cadmium, mercury, and tin were not detected. Conclusion: Analytical data of this study showed that R. steudneri and R. apetalus leaves contain the sufficient amounts of nutrients, macronutrients, micronutrients, and vitamins that the body needs for its growth and functions that can be explored in the field of the nutraceuticals and pharmaceutical industry.
Keywords: Acid-insoluble ash; Anthocyanin; HPLC; Niacin; Phytic acid; Pyridoxine; Tannin